How do somersaulters land on their feet? - Lee, D. N.; Young, D. S.; Rewt, D. (Journal of Experimental Psychology: Human Perception and Performance, 1992)
Body movements of trampolinists landing upright from forward somersaults, with eyes open and closed, were analyzed to test a theory of how braking and timing of actions are conjointly controlled. In regulating landing, rotation has to be slowed by extending the body so that it reaches the upright just as the feet hit the trampoline. Extending a theory of visual control of linear braking, it was hypothesized that upright landing is achieved by perceptually regulating body extension so as to keep the ratio angle of body to upright:rate of change of angle (the tau function of the angle) proportional to time-to-landing. The data support the hypothesis, indicate that vision improves precision of control, and argue further for the value of the tau function in the perceptual regulation of action. (PsycINFO Database Record (c) 2012 APA, all rights reserved)